Fotojornalismo subversivo: 1968 revisto pelas lentes do Correio da Manhã - Oliveira, Gil Vicente Vaz (2011)
In 1968, Correio da Manhã was one of the strongest voices against the military dictatorship, being as well a mandatory reference for readers looking for a critical view of Brazil at that time. This paper describes how the language and practices applied by its team of photographers played a decisive role in the building of what probably was, during that year, the firmest and most vigorous discourse of contention within the sphere of the national, daily press.